Primary Tupaia Javanica Hepatocyte Culture as an In Vitro Model for Human Hepatitis B Virus Infection - Kemal Fariz Kalista; Maryati Surya; Silmi Mariya; Diah Iskandriati; Irsan Hasan; Rino Alvani Gani (The Indonesian Society for Digestive Endoscopy, 2021)
Background: Hepatitis B virus (HBV) infection is still one of the biggest health problems in the world, which could lead to chronic hepatitis, cirrhosis and hepatocellular carcinoma. Treatment for HBV infection has not yet achieved a functional cure. More studies are needed to investigate human HBV (HuHBV), but the scarcity of animal models for HuHBV infection became a barrier. Recently, many studies have shown that Tupaia are suitable for the study of HuHBV. The purpose of this study was to develop a primary tupaia hepatocyte (PTH) culture from T. javanica, a species of Tupaia found in Indonesia, and to prove that HuHBV can replicate in the PTH.Method: In vitro experimental study using PTH isolated from five wild adult T. javanica in Primate Research Center, IPB University. HuHBV was taken from humans with HBsAg and HBV-DNA (+). PTH cells then were infected with HuHBV after reaching 80% confluence. Observation on PTH cells was done everyday for 20 days. Qualitative and quantitative HBsAg were measured using a CMIA while HBV-DNA and cccDNA were measured by RT-PCR.Results: A cytopathic effect was seen on day post infection (DPI)-16. HBsAg and HBV-DNA were detected from DPI-2 until DPI-18, with HBV-DNA level peaked on DPI-12. cccDNA concentration was fluctuating from DPI-2 until DPI-20 with highest level on DPI-16.Conclusion: HuHBV could infect and replicate in PTH from T. javanica can be infected with HuHBV and HuHBV can replicate in the PTH from T. javanica.